RIWAYAT ANEMIA PADA KEHAMILAN SEBAGAI PREDIKTOR KEJADIAN STUNTING PADA ANAK: LITERATUR REVIEW - Salma, Wa Ode; Alifariki, La Ode (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Anemia of pregnancy is a very large public health problem in the world, especially for women of reproductive age (WUS). Anemia of pregnancy is very risky for the baby to be born and will cause stunting in toddlers. This is because the nutritional intake obtained is not sufficient. The purpose of this study was to determine the relationship between a history of anemia in pregnancy and the incidence of stunting in children. Not all anemia of pregnancy can cause stunting in children, but it is better based on the results of this article review where there are articles that state that there is a relationship between a history of anemia and the incidence of stunting, it is hoped that mothers can prevent anemia during pregnancy. The results of this article review can be used as reference material for parties in improving services by preventing stunting in children